Slicing VET data differently: tropical seasonality and evidence-based commencement and completion policies. (2nd January 2019) - Zoellner, Don
ABSTRACT: This paper explores the results that arise from asking different, cross-disciplinary questions of vocational education and training data. Commencement and completion results from the Australian National Apprentice and Trainee Collection from a two decade-long period of time were geographically categorised into the tropical north and temperate south. Statistical analyses identified a clear difference between the two regions in the timing of cancellations and withdrawals from training contracts in the trade occupations as well as an unexpectedly strong distinction in the annual pattern of non-trade commencements in training. Regionally-specific climate variables are briefly examined to determine if there is prima facie support for a climatic explanation for the commencement of non-trade traineeships. Exploration of the data set suggests that the seasonal motivation to commence formal study in the non-trade occupations may come from sources outside the national training system and have implications for policy-making.